Desenvolvimento de um sistema embarcado para aquisição de potenciais cardíacos - Chaves, Leonardo Alves (2016)
The analysis of the report of World Health Organization shows that the number of deaths due to cardiovascular diseases is alarming. In this way, the need to monitor patients quickly and efficiently opens the way for the creation of solutions that integrate some remote monitoring devices, reducing the response time to detect heart diseases and increasing the patient's life. In this context, there is the electrocardiogram, which is a non-invasive examination that records an electrical activity generated by the heart with electrodes. The obtained signal allows to analyze the cardiac rhythm, making it possible to detect anomalies associated to its activity. Based on these premises, we have the present project, which has the objective of evaluating cardiac signals, reducing as external interference in a medical-hospital environment by means of electro-electronic instrumentation and digital signal processing.